Anti-β2 Glycoprotein I Antibodies and Platelet Activation in Patients with Antiphospholipid Antibodies: Association with Increased Excretion of Platelet-Derived Thromboxane Urinary Metabolites - Forastiero, Ricardo; Martinuzzo, Marta; Carreras, Luis O.; Maclouf, Jacques (Thrombosis and Haemostasis, 1998)
Platelet activation may contribute to the increased risk of thrombotic complications in patients with antiphospholipid antibodies (aPL). The increased urinary excretion of 11-dehydro-thromboxane B2 (11-DH-TXB2) reported in patients with lupus anticoagulant (LA) and/or anticardiolipin antibodies (aCL) reflects in vivo platelet activation. However the majority of autoimmune aPL are directed to β2 glycoprotein I (β2GPI) or prothrombin (II). We investigated the relationship of these antibodies with 11-DH-TXB2 urinary excretion in 34 patients with aPL. The urinary 11-DH-TXB2 was measured by EIA after extraction on octadecyl columns and purification on silica gel columns, which was validated by thin-layer chromatography/EIA procedure. A significantly increased excretion of 11-DH-TXB2 was found in aPL patients as compared to 18 normal controls (p <0.01). But no differences were seen in the excretion of 11-DH-TXB2 between patients with or without LA, or aCL. The number of patients with anti-II antibodies was too small to draw any conclusion. In contrast, patients with anti-β2GPI antibodies IgG at moderate/high titre (group A, n = 14) had higher levels of urinary 11-DH-TXB2 than those at low titre or negative (group B, n = 20) (p = 0.01). The group A of patients presented an increase in 11-DH-TXB2 compared to controls (p <0.001), but no statistically significant difference was found between patients from the group B and normal controls. A correlation between levels of urinary 11-DH-TXB2 and titre of antibodies was only found for anti-β2GPI-IgG (rs = 0.51, p <0.005). Our data show that the observed platelet activation in aPL patients is related to the presence of antibodies reacting with β2GPI.